The convenience of non-conventional methods for evaluation of the culinary quality of beans (Research, Society and Development, 2020)
The standard Mattson method to evaluate the cooking time of beans on breeding programs presents disadvantages. We have tested and improved a non-conventional method previously proposed to evaluate the percentage of cooked grains on an automatic pressure cooker. It showed a similar trend as Mattson’s for the cooking behavior of contrasting genotypes, but the first showed a higher correlation with sensory tests. Differently, it is closer to the Brazilian domestic bean preparation. It is a simple and more affordable procedure for application in a huge routine, once it requires a shorter time to run simultaneously a larger number of samples with confident results. Its positive correlation with sensory analysis helps breeders to select promising genotypes from early breeding generations to attend consumer demands more efficiently. We recommend the standard method be used preferably to evaluate the advanced generations to validate the cooking quality of selected materials and to attend cultivar releasing normative.